2016
DOI: 10.1007/s11434-015-0982-x
|View full text |Cite
|
Sign up to set email alerts
|

From strangelets to strange stars: a unified description

Abstract: The conventionally separated treatments for strangelets and strange stars are now unified with a more comprehensive theoretical description for objects ranging from strangelets to strange stars. After constraining the model parameter according to the Witten-Bodmer hypothesis and observational massradius probability distribution of pulsars, we investigate the properties of this kind of objects. It is found that the energy per baryon decreases monotonically with increasing baryon number and reaches its minimum a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 56 publications
(71 reference statements)
2
24
0
Order By: Relevance
“…For larger A, due to Coulomb repulsion, a strangelet can carry charge only on its surface and the surface structure starts to converge. This was also predicted by the UDS model, where larger SQM objects indicate a constant surface charge density [33][34][35][36][37]. To give a more detailed picture on the internal structure of strangelets, in Fig.…”
Section: Resultssupporting
confidence: 62%
“…For larger A, due to Coulomb repulsion, a strangelet can carry charge only on its surface and the surface structure starts to converge. This was also predicted by the UDS model, where larger SQM objects indicate a constant surface charge density [33][34][35][36][37]. To give a more detailed picture on the internal structure of strangelets, in Fig.…”
Section: Resultssupporting
confidence: 62%
“…Steiner et al 19 showed that the ground state of the CFL phase is color neutral and that color neutrality forces electric charge neutrality. Models of unmagnetized quark nuggets by Xia et al 11 and by Zhitnitsky et al 42 predict different small (i.e. the ratio of electric charge per baryon mass is much less than one), non-zero internal electric charges, but both predict charge neutralizing surface layers.…”
mentioning
confidence: 99%
“…Macroscopic quark nuggets are also called strangelets [6], nuclearites [7], AQNs [8], and slets [9], are theoretically predicted objects composed of up, down, and strange quarks in essentially equal numbers. They form a subset of Macros [10], the more general term for massive dark-matter.…”
Section: Supplementary Materials: Nonementioning
confidence: 99%
“…Steiner, et al [13] showed that the ground state of the CFL phase is color neutral and that color neutrality forces electric charge neutrality, which minimizes electromagnetic emissions. However, Xia, et al [9] found that quark depletion causes the ratio Q/A of electric charge Q to baryon number A to be non-zero and varying as Q/A ~0.32 A -1/3 for 3 < A < 10 5 . In addition to this core charge, they find that there is a large surface charge and a neutralizing cloud of charge to give a net zero electric charge for sufficiently large A.…”
Section: Supplementary Materials: Nonementioning
confidence: 99%